A diverse intrinsic antibiotic resistome from a cave bacterium - Andrew C. Pawlowski (Nature Portfolio, 2016)
Antibiotic resistance is common in environmental bacteria, including those living in isolated caves. Here, Pawlowskiet al. study one of these bacterial strains, showing that it is resistant to most clinically used antibiotics through a remarkable variety of mechanisms, some of which are new to science.